Ceratonia siliqua leaves exert a strong ROS-scavenging effect in human neutrophils, inhibit myeloperoxydase in vitro and protect against intestinal fluid and electrolytes secretion in rats. Issue 70 (11th July 2016) - Rtibi, Kaïs; Jabri, Mohammed-Amine; Selmi, Slimen; Sebai, Hichem; Amri, Mohamed; El-Benna, Jamel; Marzouki, Lamjed
Abstract : Chronic inflammation and oxidative stress are induced by biological, chemical and physical factors which are, in turn, associated with an increased risk of several human diseases. Abstract : Chronic inflammation and oxidative stress are induced by biological, chemical and physical factors which are, in turn, associated with an increased risk of several human diseases. Plants are a large source of new bioactive molecules with therapeutic potential. In this respect, the present study was designed to investigate the effects of a Ceratonia siliqua L. leaf aqueous extract (CSLAE) on human neutrophil reactive oxygen species (ROS) production, in vitro myeloperoxidase (MPO) activity and expression as well as the small intestinal fluid and electrolyte secretion. Neutrophils were isolated from whole human blood of healthy volunteers using the ficoll–dextran method and ROS generation and H2 O2 were measured by luminol amplified chemiluminescence. Superoxide anion generation was also detected by chemiluminescence using the lucigenin method. MPO activity and quantity were measured by the tetramethylbenzidine oxidation method and Western blotting analysis. Concerning the in vivo part, fasted male rats received by gavage either the vehicle (NaCl, 0.9%), the extract at various doses (50, 100 and 200 mg kg −1 ) or clonidine (1 mg kg −1 ). An activated charcoal suspension was administered by oral gavage. Thirty minutes after receiving the charcoal meal, rats were euthanized and the small intestine was removed. The length of the small intestine and the distance traveled by the charcoal were recorded. Castor oil-induced hypersecretion in Wistar rats was treated with administration of CSLAE (50, 100 and 200 mg kg −1 ) and antidiarrheal drug, Atropine (0.1 mg kg −1 i.p.). CSLAE inhibited luminol-amplified chemiluminescence of (PMA)-stimulated neutrophils in a concentration-dependent manner and is able to scavenge superoxide anions and hydrogen peroxide. The CSLAE also reduces significantly and dose-dependently MPO activity and expression. On the other hand, in vivo studies showed that the CSLAE decreased notably and dose-dependently the GIT activity, intestinal fluid and electrolyte concentration. The chemical analysis using a HPLC technique showed that the CSLAE is rich in phenolic compounds, especially kaempferol, tannic acid and catechin hydrate. The intended neutrophil inhibition is introduced as a part of a new strategy for pharmacological modulation of chronic inflammatory and oxidative stress processes. On the basis of these findings, it can be also assumed that CSLAE could be a potential source for novel discovery for antidiarrhoeal drug development.